Exploration of factors that influence divorce: Voices of divorcees in Lagos, Nigeria - Samuel Ojima Adejoh; Olubukola Wellington; Waziri Adisa; Franca Attoh; Tolani Aderonke Eliphus (Social Work & Society, 2024)
Globally, studies have identified different ideologies in explaining the risk factors for divorce. However, few studies have examined health-related factors in the termination of marital union. This study explored how health-related factors- of Sexual Transmitted Diseases (STDs), lack of sexual desires, genotype and domestic violence influence divorce in Lagos, Nigeria. The study was conducted in Lagos Island, Lagos. Data were collected from 30 consenting divorcees comprising males and females through in-depth interviews. Participants' selection was achieved through a purposive sampling technique. Findings revealed that domestic violence, infertility and other health related factors, such as incompatible genotype, sexually transmitted diseases (STDs) and lack of sexual desires, are potential causes of divorce. Therefore, intending couples need to ascertain the compatibility of their genotype with their spouses through medical screening. Couples battling with any health challenge in their marital union should seek help from licensed health professionals to help mitigate the potential impact the challenge may have on their marital union as well as engage the services of social workers in finding solution to the problem of domestic violence.